Telemedicine - assesment of society's opinion - Magdalena Kamila Zawiślak; Marcin Zaniuk; Marta Kozłowska; Patryk Zimnicki; Zuzanna Wujec (Kazimierz Wielki University, 2021)
During the COVID-19 pandemic, it is necessary to use some safety measures due to decrease spreading of the virus. One of them is introducing teleconsultations as a form of medical consultation. It allows patients to talk with the doctor without visiting the hospital. The aim of the study is to present the society's opinion on teleconsultations and its most common disadvantages. The method of the study was an online survey, conducted on 68 people, whose answers were statistically analyzed. During the pandemic, 85% of the respondents took part in the teleconsultation. After thay, they rated quality of the teleconsultation form 1 to 5, where 5 was the highest rate. Only 26,8% of them rated their teleconsultation 5, 17,9% - 4, 16,1% - 3, 26,8% - 2 and 12,5% - 1. Most of the respondents decided to took part in the teleconsultation because they needed a prescription (53%). According to respondents' opinion, the most important advantages of the teleconsultation are: ability to stay home (59,7%), lower risk of infection (35,8%), quick help (22,4%) and ability to have the prescription without going out (73,1%). The most important disadvantages were: lack of ability of physical examination (91%), problems with communication (40,3%), problems with describing their own symptoms (43,3%), problems with contacting a doctor (58,2%) and higher risk of wrong diagnosis (82,1%). Teleconsultations provide patients' safety, however, they are associated with danger of the wrong diagnosis. Although, most patients (73%) would like to be able to take part in the teleconsultation after the pandemic. Because of that, it is crucial for modern medicine to improve the quality of teleconsultation and to learn, how to communicate with patients during the remote conversations.